Characterization and electrochemical corrosion behaviour of FSPed WE43/nano-SiC surface composite. (2020) - Singla, Shivali; Singh Kang, Amardeep; Sidhu, T.S.
Abstract: Treating magnesium (Mg) through friction stir processing (FSP) has been widely acknowledged for enhancing the mechanical and tribological properties by bringing favourable microstructural refinement and homogenization of reinforcements. The present research work is aimed to fabricate nano-sized silicon carbide (SiC) reinforced Mg-based composites through FSP. The effect of different types of FSP tools' geometries, travel speed, and rotational speed on the microstructure and corrosion resistance was investigated. The processing has been carried out for three numbers of passes in order to ensure the uniform distribution of the reinforcement. The metallurgical characteristics of as fabricated composites have been studied to find out their correlations with the selected in-process variables. Further, corrosion resistance of the samples has also been determined for the prepared specimens. It has been found that the quality characteristics of the composites have been greatly influenced by the FSP tool pin geometry. The grain size of the Mg alloy has been significantly reduced from 22.42 to 8.17 µm. Moreover, the degradation rate of the unprocessed Mg alloy is found to be 0.44gm/cm2.hr, higher than the processed WE43/SiC composite.